International Scientific Collaboration Links of Central Eastern European Countries Measured Through Publications (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The countries of Central Eastern Europe (CEE) are lagging behind Western-Europe regarding scientific performance in the field of economics. A way to improve the quantity and quality of scientific output is to establish international scientific links with developed countries. The aim of this study is to analyze the international cooperation of Central and Eastern European countries in the field of economics. International scientific collaborations are measured through publications. The analyzed time period is 1996-2014. The used database is Scopus. Using network theory tools, it is shown that researchers from the CEE countries tend to publish more with researchers from Western Europe or the USA, rather than with researchers from the CEE region. It appears that geographical distance does not play a significant role in choosing international scientific collaboration partners. Policy decision makers should focus more on supporting and promoting research and educational mobility as these can help the CEE countries in the scientific catching-up process.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.